1999
DOI: 10.1017/s0021963099004746
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in International Adoptees as Teenagers and Young Adults. An Epidemiological Study

Abstract: Sweden has now around 38,000 individuals who have been adopted from other countries. Most often they are transracially adopted and have a different appearance from their new parents--"visible" adoptions. This study was made to explore the mental health of a teenager/young adult group that arrived with their families in the southernmost county of Sweden between 1970 and 1977. They were placed through the largest Swedish adoption agency at that time. One hundred and forty-seven families and their 211 adopted chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 12 publications
9
86
1
3
Order By: Relevance
“…It is further in line with studies showing that scores of family functioning and quality of peer relationships is correlated to mental health outcomes among adolescents who have been adopted (Cederblad et al, 1999;McGuinness et al, 2005). However, these studies did not compare the associations found for adoptees with non-adopted peers.…”
Section: Discussionsupporting
confidence: 81%
“…It is further in line with studies showing that scores of family functioning and quality of peer relationships is correlated to mental health outcomes among adolescents who have been adopted (Cederblad et al, 1999;McGuinness et al, 2005). However, these studies did not compare the associations found for adoptees with non-adopted peers.…”
Section: Discussionsupporting
confidence: 81%
“…Cependant à l'heure actuelle, il est impossible d'établir un lien de causalité directe entre adoption et troubles psychiatriques. Plusieurs études montrent en revanche une corrélation positive entre le risque de troubles du comportement à l'adolescence et l'âge auquel l'enfant a été adopté [38][39][40][41]. En effet, les conditions de vie adverses de l'enfant avant l'adoption sont un facteur de risque majeur.…”
Section: Discussionunclassified
“…Cultural socialization is related to personal growth and this association is fully mediated by ethnic identity strength. Cederblad et al (1999) . 147 adoptive families including 211 adopted adolescents or young adults aged 13-27 .…”
Section: Studies On Ethnic Identity and Psychological Well-beingmentioning
confidence: 99%